2011
DOI: 10.1007/s11060-011-0758-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher topoisomerase 2 alpha gene transcript levels predict better prognosis in GBM patients receiving temozolomide chemotherapy: identification of temozolomide as a TOP2A inhibitor

Abstract: The search for molecular markers which predict response to chemotherapy is an important aspect of current neuro-oncology research. MGMT promoter methylation is the only proved marker of glioblastoma. The purpose of this study was to assess the effect of topoisomerase expression on glioblastoma survival and study the mechanisms involved. The transcript levels of all isoforms of the topoisomerase family in all grades of diffuse astrocytoma were assessed. A prospective study of patients with glioblastoma treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…In addition to its roles in DNA synthesis and transcription, and chromosomal segregation during mitosis, Tsavaris et al (43) has reported that TOP2A is also a sensitive and specific marker of actively proliferating cells. In the present study, TOP2A was found to be significantly involved in the prognosis of patients with glioblastoma, which was consistent with numerous previous studies (4446). NEK2 encodes a serine/threonine-protein kinase, which is involved in mitotic regulation (47).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to its roles in DNA synthesis and transcription, and chromosomal segregation during mitosis, Tsavaris et al (43) has reported that TOP2A is also a sensitive and specific marker of actively proliferating cells. In the present study, TOP2A was found to be significantly involved in the prognosis of patients with glioblastoma, which was consistent with numerous previous studies (4446). NEK2 encodes a serine/threonine-protein kinase, which is involved in mitotic regulation (47).…”
Section: Discussionsupporting
confidence: 93%
“…Apart from effects on neuroinflammation, effects on DNA damage, which is an emerging disease mechanism in ALS-FTD [ 50 ], could be of interest. Top2a and GRN are upregulated in glioblastomas [ 51 , 52 ] and GRN overexpression was shown to protect against DNA damage induced by the Top2a inhibitor tomozolomide in glioblastoma cell lines [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that temozolomide is a TOP2A inhibitor thus explaining the phenomenon of TOP2A overexpressing tumors being more sensitive to temozolomide chemotherapy with resultant longer survival of patients. Further, down regulation of TOP2A using RNA interference in glioma cells resulted in temozolomide chemosresistance [38]. Unlike these three genes, CALCRL ( Calc itonin r eceptor- l ike), has been shown to activate angiogenesis and was found to be expressed in endothelial cells of microvascular proliferations and in the neighbouring tumor cells of glial tumors [39], [40].…”
Section: Discussionmentioning
confidence: 99%